Beyond 2020: Moving from objectives to governance to master ever more pressing challenges (Transactions of the Association of European Schools of Planning, 2020)
The adoption of the Territorial Agenda 2030, some 20 years after the adoption of the European Spatial Development Perspective (ESDP) (European Commission, 1999) presents an opportunity to both look back on what has been achieved and envisage developments for the next 20 years. This paper starts with some personal reflections on the aspirations put forward in the ESDP and some key achievements. The main part of the paper then concentrates on what might be done differently over the next 20 years. It is argued that because the world has changed substantially since 1999 it is time to breathe new life into the original objectives of the ESDP and support them with clear governance and implementation tools. Furthermore, the geographical coverage ought to be extended to cover the Western Balkans. The final section offers an outlook on what we might want to see when looking back again 20 years from now.